2004
DOI: 10.1080/09614520410001686124
|View full text |Cite
|
Sign up to set email alerts
|

Developing indicators to assess women's empowerment in Vietnam

Abstract: From mid-1999From mid- to mid-2001, the authors carried out a qualitative study in rural Vietnam to explore relationships between gender equity and reproductive health. One of the study's objectives was to develop culturally appropriate indicators of women's empowerment, specific to the Vietnamese context. This paper describes the process of developing, testing, and refining the empowerment indicators, presents some of the findings, and discusses the methodological challenges that need to be addressed. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Contraceptive use in response to national fertility regulation, together with its costs and risks, is primarily the woman’s responsibility [29]. Comparably, Santillan’s study (2004) found that traditional gender norms encouraged women’s tolerance of contraceptive responsibilities and side effects and discouraged women with gynecological health problems from seeking treatment [12]. In our subsequent survey of 1181 female students at the two universities, we asked to what extent they agreed with the statement ‘If an unmarried woman obtains a gynecological examination, she will be denigrated?’ On a 7-point scale, 12.2% slightly agreed, 17.5% agreed and 4.5% completely agreed [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contraceptive use in response to national fertility regulation, together with its costs and risks, is primarily the woman’s responsibility [29]. Comparably, Santillan’s study (2004) found that traditional gender norms encouraged women’s tolerance of contraceptive responsibilities and side effects and discouraged women with gynecological health problems from seeking treatment [12]. In our subsequent survey of 1181 female students at the two universities, we asked to what extent they agreed with the statement ‘If an unmarried woman obtains a gynecological examination, she will be denigrated?’ On a 7-point scale, 12.2% slightly agreed, 17.5% agreed and 4.5% completely agreed [30].…”
Section: Discussionmentioning
confidence: 99%
“…There are very few credible peer-reviewed studies applicable to Vietnam that explore women’s self-perceptions regarding gender relations. Santillan’s work to develop indicators to assess women’s empowerment partially filled this measurement gap [12]. However, this study was designed to measure women’s empowerment in sexual and reproductive health rather than gender relations, and it was conducted in two northern provinces of Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“…We went through an iterative process to develop our construct of reproductive autonomy. We examined existing qualitative and quantitative research regarding women's empowerment/autonomy/status and how it affects such reproductive outcomes as contraceptive use, fertility, unintended pregnancy, and abortion (Mason 1986;Isvan 1991;Heinrich 1993;Abadian 1996;Hindin 2000;Mason and Smith 2000;Pulerwitz, Gortman, and DeJong 2000;Blanc 2001;Kabeer 2001;Malhotra, Schuler, and Boender 2002;Morgan et al 2002;Harper, Minnis, and Padian 2003;Santillán et al 2004;Jones 2006;McGinn and Allen 2006;Purdy 2006;Kishor and Subaiya 2008;Ip, Sin, and Chan 2009;Mumtaz and Salway 2009;Peyman et al 2009;DeRose and Ezeh 2010;Grady et al 2010;Lee-Rife 2010;Miller et al 2010a;Bogale et al 2011;Pande et al 2011). Specifically, we documented how each of these studies conceptualized women's empowerment.…”
Section: Conceptual Framework Developmentmentioning
confidence: 99%
“…Finally, management of coercion was conceptualized as having the ability to avoid and/or respond appropriately to coercion regarding contraceptive use, pregnancy, and childbearing. Several studies were particularly influential in our development of this conceptual model (Pulerwitz, Gortman, and DeJong 2000;Blanc 2001;Santillán et al 2004;Jones 2006;Purdy 2006;Miller et al 2010a). For example, Miller and colleagues' (2010a and 2010b) documentation of pregnancy coercion (when a partner commits specific acts to promote pregnancy when the woman wants to prevent pregnancy, such as hiding contraceptives or pressuring a woman not to use them) influenced our inclusion of the concept of management of coercion.…”
Section: Conceptual Framework Developmentmentioning
confidence: 99%
“…We contribute to accounts of marriage relations in the context of labour migration by examining the neglected reproductive dimensions of these 'strategic life choices' (Santillan et al, 2004). Taking reproduction more seriously means engaging with the way in which 'making a life' (Whitehead, 2002: 577) is not only about a productive living, but is also about the creation and maintenance of familial and social relationships over time.…”
Section: Introductionmentioning
confidence: 99%